Pengaruh Motivasi, Komitmen Organisasi Dan Due Professional Care Terhadap Kualitas Audit - Muren, Louis Albertoaran; Pangaribuan, Hisar (Lembaga Riset Ilmiah, 2022)
This study aims to examine the effect of the independent variables of motivation, organizational commitment, and due professional care on the dependent variable of audit quality. The population in this study were all auditors, both junior and senior auditors who worked in 5 public accounting firm in Jakarta with a total of 57 respondents. The sampling technique in this study used the Convenience Sampling Method and the data used in this study was primary data. In this study, the authors use Descriptive Statistical Test, Classical Assumption Tes (normality test, multicollinearity test, heteroscedasticity test), Hypothesis Test (coefficient of determination, t test, f test) and Multiple Linear Regression Analysis to be able to analyze the data used and use SPSS software version 25. Based on the results of research through several tests carried out, it can be concluded that motivation, commitment organization, and due professional care have a positive effect on audit quality. Keywords: Motivation, Organizational Commitment, Due Professional Care, and Audit Quality